Evaluation of probabilistic modelling approaches against data on leaching of isoproturon through undisturbed lysimeters - Beulke, Sabine; Brown, Colin D.; Dubus, Igor G.; Fryer, Christopher J.; Walker, Allan (Elsevier, 2004)
This study evaluated probabilistic modelling approaches against data on leaching of isoproturon through two contrasting soil types. Leaching through undisturbed lysimeters from a sandy loam (Wick series) and a moderately structured clay loam (Hodnet series) was investigated in seven replicates. The variability of soil properties and of sorption and degradation of isoproturon was estimated by taking 6-14 samples within the areas of lysimeter extraction in the field. Normal distributions were assigned to Koc and DT50 and a large number of values for these two parameters were sampled from each distribution. Parameter values were used to simulate movement of isoproturon through the lysimeters with the preferential flow model MACRO. Uncertainty in output distributions was compared with the variability of measured data. A constrained probabilistic assessment varying only degradation and sorption properties was sufficient to match the observed variability in cumulative leaching from the coarse-textured Wick soil (CV = 79%). Variation of pesticide properties alone could not match observed variability in cumulative leaching from the structured Hodnet soil (CV = 61%) and variability in a number of soil properties was incorporated. For both soils, constrained probabilistic approaches where only the top few most sensitive model inputs were varied were sufficient to match or exceed observed variability.
Keywords: Groundwater